Cerebrospinal fluid proteomics reveal potential protein targets of JiaWeiSiNiSan in preventing chronic psychological stress damage - Han-Zhang Wang; Wu-Long Luo; Ning-Xi Zeng; Hui-Zhen Li; Ling Li; Can Yan; Li-Li Wu (Taylor & Francis Group, 2021)
Context Chinese herbal formula JiaWeiSiNiSan (JWSNS) has been widely used to prevent stress-induced neuropsychiatric ailments in clinics and proven to have therapeutic anti-stress effects on rats. However, the mechanism remains unclear. Objective Based on the proteomics of cerebrospinal fluid (CSF), this study explores the possible mechanism and target proteins of JiaWeiSiNiSan raising stress resilience and preventing stress damage. Materials and methods A 6-week Chronic Unpredictable Mild Stress (CUMS) model was applied on adult Wistar male rats to observe the effects of JWSNS on improving mental stress resilience. Tandem Mass Tag (TMT) proteomics and bioinformatics analysis were used to screen and analyze differentially expressed proteins (DEPs) in CSF. Parallel Reaction Monitoring (PRM) was used to validate target DEPs. Results Significantly decreased sucrose preference, locomotion activity level and accuracy of T-maze, as well as increased immobility time, were observed in CUMS rats compared to CON rats while JWSNS improved above depression-like behaviours. The quantitative proteomics and bioinformatics analysis showed that JWSNS decreased the expression of Rps4x, HSP90AA1, Rps12, Uba1, Rsp14, Tuba1b in CUMS rats CSF (p < 0.05, FDR < 0.5). Immunofluorescence results showed that the number of BrdU/DCX positive cells (p < 0.01) and the relative number of neurons (p < 0.01) in the hippocampus dentate gyrus (DG) of the JSWNS group significantly increased, compared with the CUMS group. Conclusions JWSNS could increase mental stress resilience and prevent stress damage by regulating proteins in CSF. This study provides a scientific basis for further study on Chinese formulas preventing mental illness.